The Relationship Between Attention Parents and Student’s Attitudes towards Juvenile Delinquency - Bertha Mazela Febriani; Herman Nirwana (Jurnal Neo Konseling, 2020)
The background of this research the number of students who have an attitude of juvenile delinquency is on the low category, attitude is the tendency level that is positive or negative relating to the object of psychology. One of the factors suspected to affect the attitude is attention parents. This study aims to: (1) describe the student’s attitudes toward juvenile delinquency, (2) describe the attention parents, and (3) test a significant positive relationship between attention parents with student’s attitudes toward juvenile delinquency.This study uses quantitative methods with descriptive correlational. The study population is 728 students Junior High School  25 Padang registered in July-December  of periode  academic 2019/2020 and a sample of 238 students were selected by stratified random sampling. The instrument used was a questionaire the attention  parents with reliability 0.097 and questionnaires student’s attitudes toward juvenile delinquency with the reliability of 0.862. Data were analyzed by using descriptive statistics and Pearson Product Moment technique.The findings show that: (1) attention parents are in good enough category, (2) students' attitudes toward juvenile delinquency are in the good category, (3) and there is a significant positive relationship between attention  parental attitudes toward juvenile delinquency with a correlation coefficient of 0.234 and a significance level of 0.000.